Unrelated Future Costs and Unrelated Future Benefits: Reflections on NICE Guide to the Methods of Technology Appraisal. (August 2016) - Morton, Alec; Adler, Amanda I.; Bell, David; Briggs, Andrew; Brouwer, Werner; Claxton, Karl; Craig, Neil; Fischer, Alastair; McGregor, Peter; van Baal, Pieter
Summary: In this editorial, we consider the vexing issue of 'unrelated future costs' (for example, the costs of caring for people with dementia or kidney failure after preventing their deaths from a heart attack). The National Institute of Health and Care Excellence (NICE) guidance is not to take such costs into account in technology appraisals. However, standard appraisal practice involves modelling the benefits of those unrelated technologies. We argue that there is a sound principled reason for including both the costs and benefits of unrelated care. Changing this practice would have material consequences for decisions about reimbursing particular technologies, and we urge future research to understand this better. Copyright © 2016 John Wiley & Sons, Ltd.